The impact of democracy, corruption and military expenditure on environmental degradation: Evidence from top six Asean countries - Zandi, Gholamreza; Haseeb, Muhammad; Zainal Abidin, Irwan Shah (Gyandhara International Academic Publications, 2019)
Purpose of the study:The current study aims to examine the relationship between corruption, democracy, military expenditure and environmental degradation in a panel of six ASEAN countries including Malaysia, Indonesia, Philippines, Thailand, Singapore and Vietnam using a panel data from 1995 to 2017. Methodology:In addition, the current study is unique in applying the sophisticated methods of panel Fully Modified Ordinary Least Square (FMOLS) and Dynamic Ordinary Least Square (DOLS) that have been adopted in several earlier quality research. Main Findings:The results of panel estimations conclude that corruption, military expenditure,and democracy have a noteworthy and significant impact on carbon dioxide emission in ASEAN countries. The results of FMOLS and DOLS confirm that there is a positive and significant impact of military expenditure and corruption on carbon dioxide emission. However, we found a negative and significant impact of democracy on carbon dioxide emission in all selected ASEAN countries. Implications:In general, the consequences of both statistical estimations affirm that corruption, democracy,and military expenditure are the critical and noteworthy determinants of carbon dioxide emission in ASEAN nations.